Les cultes isiaques et les Italiens entre Délos, Thessalonique et l’Eubée - Paraskevi Martzavou (Pallas, 2010)
The examination of the epigraphic, archeological and literary data shows similarities as regards Isiac cults between Delos, Euboea and Thessalonica, in the ritual and social profile of the votaries. Those similarities can be explained by migrant Italians, the Salarii for instance, chiefly in the second half of the Ist century B.C. as a consequence of the mithridatic wars and the decline of Delos. The relationship between “Italian traffickers” and Isiac cults enables us to enquire into the institutional and social contexts but also into the nature of the religious change itself.